2017
DOI: 10.7150/thno.18927
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antitumor efficacy of biocompatible magnetosomes for the magnetic hyperthermia treatment of glioblastoma

Abstract: In this study, biologically synthesized iron oxide nanoparticles, called magnetosomes, are made fully biocompatible by removing potentially toxic organic bacterial residues such as endotoxins at magnetosome mineral core surfaces and by coating such surface with poly-L-lysine, leading to magnetosomes-poly-L-lysine (M-PLL). M-PLL antitumor efficacy is compared with that of chemically synthesized iron oxide nanoparticles (IONPs) currently used for magnetic hyperthermia. M-PLL and IONPs are tested for the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 60 publications
1
74
0
Order By: Relevance
“…Poly( l ‐lysine)‐coated magnetosomes have been used successfully for experimental magnetic hyperthermia treatment in a murine model of glioblastoma, an aggressive, fast‐growing brain tumor. [ 340 ] Similarly, magnetosomes extracted from Magnetospirillum gryphiswaldense MSR‐1 culture have been utilized, after purification, as theranostic agents in an in vivo murine subcutaneous model of colon carcinoma [ 341 ] as well as an in vivo murine xenograft model of glioblastoma. [ 342 ] Instead of using bioengineered harvested magnetosomes, a recent paper reported the use of live M .…”
Section: Applicationsmentioning
confidence: 99%
“…Poly( l ‐lysine)‐coated magnetosomes have been used successfully for experimental magnetic hyperthermia treatment in a murine model of glioblastoma, an aggressive, fast‐growing brain tumor. [ 340 ] Similarly, magnetosomes extracted from Magnetospirillum gryphiswaldense MSR‐1 culture have been utilized, after purification, as theranostic agents in an in vivo murine subcutaneous model of colon carcinoma [ 341 ] as well as an in vivo murine xenograft model of glioblastoma. [ 342 ] Instead of using bioengineered harvested magnetosomes, a recent paper reported the use of live M .…”
Section: Applicationsmentioning
confidence: 99%
“…The distinctive characteristics of BMs suggested that they could be used as an effective vehicle, particularly as a potential magnetic carrier for drugs. BMs have been used as vehicles for antibodies, nucleic acids, and proteins in the laboratory . In our study, we developed a convenient way to conjugate antibodies to BMs.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetosomes are small in size (40–120 nm) and are covered with a stable lipid membrane, which allows the magnetosomes to disperse very well . The bilayer membrane component of BMs contains many amino groups, which can be combined with biological molecules that include enzymes, antibodies, and antitumor medicines . Many in vitro results have demonstrated that BMs have many advantages over artificial iron oxide nanoparticles, particularly when the nanoparticles are used for biological applications .…”
Section: Introductionmentioning
confidence: 99%
“…Using magnetotactism coupled to a system of oxygen detection (aerotactism), MTB then use their flagella to propel themselves toward the oxic-anoxic transition zone, where the oxygen concentration is optimal for their development and for magnetosome synthesis (Lefèvre and Bazylinski, 2013). Magnetosomes consist of magnetite minerals surrounded by a biological membrane (e.g., Faivre and Schüler, 2008;Le Fèvre et al, 2017;Arakaki et al, 2018). Using these bacteria, it has been possible to produce nanoparticles that fulfill most of the criteria mentioned above (Alphandéry, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, MSR-1 magnetites display an organization in chains that prevents their aggregation (Heyen and Schüler, 2003), have high crystallinity, homogenous size distribution and improved heating properties in comparison to chemically synthesized IONP Mandawala et al, 2017). Hence, these biological nanoparticles have been considered for various medical applications, especially for tumor nanoparticle-mediated hyperthermia treatments (Alphandéry et al, 2017;Le Fèvre et al, 2017). Compared with other species, MSR-1 is the species that can reach the largest magnetosome production yield (MPY), making it the best candidate for producing magnetosomes for medical applications, as reported elsewhere by comparing the MPY obtained from the different MTB species, i.e., MSR-1, AMB-1, MS-1, MV-1 (Ali et al, 2017).…”
Section: Introductionmentioning
confidence: 99%